Improving Early Childhood Patience by Using a Storytelling Approach - Yayuk Titis Ningsih; Cicilia Ika Rahayu Nita; Sarah Emanuel Hariyono (CV. Creative Tugu Pena, 2025)
Patience is an important aspect of early childhood social-emotional development, as it plays a role in children's ability to regulate emotions, wait for their turn, and complete tasks. Initial observations at Al Azhar Playgroup (KB Al Azhar) indicated that most children aged 4–5 years still demonstrated impatient behavior during learning activities. This study aims to improve early childhood patience through the implementation of a mindfulness approach using storytelling media. The research employed a qualitative approach with a Classroom Action Research (CAR) design conducted in two cycles, consisting of the stages of planning, action implementation, observation, and reflection. The research subjects were 15 children aged 4–5 years at KB Al Azhar. Data were collected through observation, interviews, and documentation, while data analysis used descriptive qualitative analysis techniques. The results showed that the implementation of the mindfulness approach through storytelling media significantly improved children's patience. Children became more able to wait for their turn, regulate their emotions, follow rules, and complete activities calmly. Therefore, the mindfulness approach through storytelling media is effective as a learning strategy to develop patience in early childhood.